Impacts des houles exceptionnelles sur le littoral ivoirien du Golfe de Guinée - Konan, Konan Ernest; Abe, Jacques; Aka, Kouamé; Neumeier, Urs; Nyssen, Jan; Ozer, André (Géomorphologie : relief, processus, environnement, 2016)
This study integrates the impacts of swells with significant morphologic impact in the analysis of the coastal sediment budget and of coastline mobility; in this case, the swells occurring in August 2007 on the coast of the Gulf of Guinea, east of Abidjan. Swells were not often taken into account in the evaluation of the mobility of that coastline, for which all modifications (retreat and accretion) need to be taken into account. For this study, we carried out a diachronic analysis of aerial photographs (1979-1989) and we established a series of topographic profiles (2007-2009), allowing to quantify volumes of deposited or eroded coastal sediments. The application of these methods shows that the coastal erosion rate at Port-Bouet bay and Assinie beaches, which generally does not exceed 1.5 m/y, is exacerbated over short periods by strong swells from the South Atlantic Ocean. Some of them are of seismic origin such as those that submerged and eroded part of the Ivorian coast during the night from 13 to 14 August, 2007. The coastline retreated between 2.3 and 18 m in one tidal cycle, causing significant damages in Port-Bouet (Abidjan Bay) where a dense population and several economic activities are located. Considering the long-term evolution of these 2 coastal segments, this swell which strongly eroded the beaches in Ivory Coast in August 2007 appears as an exceptional event, as volumes of sand eroded from all the beach profiles were significant. The studied coastline is not only continuously eroding, but it has also a high sensitivity to exceptional swells. Cette étude intègre les impacts des houles d’exceptionnelles dans l’appréciation de la mobilité du budget sédimentaire et du trait de côte du cordon littoral ivoirien à l’est d’Abidjan. Les évènements n’ont pas été souvent pris en compte dans l’évaluation de la mobilité du trait de côte du littoral ivoirien, quand on sait qu’une vitesse moyenne de l’évolution d’une côte est le bilan des mouvements (érosion/engraissement) sur celle-ci. La méthode ...